RELIABILITAS ALAT UKUR, JENIS-JENIS, CARA PENGUKURAN DAN FAKTOR-FAKTOR - Achmad Rasyid Ridha; Sudarto; Fajarullah Al Ghifari (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Reliability is a series of measurements or a set of measuring instruments that have consistency when measurements made with the measuring instrument are carried out repeatedly. Reliability is one of the criteria that must be met by a measuring instrument before being used to collect data. The concept of reliability refers to the consistency of the score results on the items contained in the questionnaire, so that the reliability test actually examines the accuracy of the measurement scales of the research instrument. A research instrument, for example a questionnaire, is declared reliable if the instrument can provide consistent score results in each measurement. Thus, the measuring instrument (statement items/questions) continues to provide consistent measurement results at different times.